KONTROL STRUKTUR TERHADAP ALTERASI DAN MINERALISASI PADA CEBAKAN EPITERMAL PROSPEK SECANG, KECAMATAN CAMPUR DARAT, KABUPATEN TULUNG AGUNG, PROVINSI JAWA TIMUR: STRUCTURAL CONTROL ON ALTERATION AND MINERALIZATION OF EPITHERMAL DEPOSIT SECANG PROSPECT, CAMPUR DARAT SUB DISTRICT, TULUNG AGUNG DISTRICT, EAST JAVA PROVINCE - Fadilah, Rizqi; Vanessa, Agata; Patonah, Aton; Haryanto, Iyan (Buletin Sumber Daya Geologi, 2025)
The study area is located within the administrative district of Campurdarat Subdistrict, Tulungagung Regency, East Java Province. This research aims to analyze the role of geological structures on alteration and mineralization processes using geological and alteration mapping method, joint measurement, petrographic and mineragraphic analysis, and spectral data interpretation. The geological mapping results indicate that the lithostratigraphy of the study area, from youngest to oldest, consists of Alluvial Unit (Sa), Limestone Unit (Sbg), Volcanic Breccia Unit (Sbv), and Andesite Lava Unit (Sla). The geological structures include faults and joints, formed through a wrench fault mechanism, indicating left-lateral movement with the formation of a transpressional pop-up structure. Alteration zones belong to the high-sulfidation epithermal deposit system, consisting of four alteration types, comprising silicifaction, advanced argillic, argillic, and propylitic. Mineralization in the study area is associated with veins and vuggy quartz. Ore minerals present include pyrite, chalcopyrite, sphalerite, marcasite, magnetite, rutile, and covellite. Alteration and mineralization in the study area are controlled by northeast-southwest and northwest-southeast strike-slip faults. Faults in the study area have caused alteration overprinting and fault zones.